Development of beef jerky from carabeef (Bubalus Bubalis) - Imbao, Anna Liza B.
ABSTRACT The feasibility of developing a product formulation of beef jerky from carabeef was undertaken. The effect of three different salt/sugar/pepper combination on the physico-chemical and sensory properties and the storage characteristics of the preferred formulation was studied. Results of the objective and sensory evaluation showed that the optimum carabeef jerky formulation was that of Formulation I which contained 1.70% salt, 3.22% sugar and 0.215% pepper.The use of the formulation employing such a combination resulted in a reddish brown product with a leathery texture and a spicy hot flavor. Sensory evaluation results revealed that among the three formulations, color and texture did not differ significantly while a significant difference was noted on flavor and general acceptability. Moisture content and water activity displayed increasing trends during storage at room temperature for three months. However, no significant difference in sensory qualities was observed. The same was true for the microbial load which showed no positive growth all throughout the three-month storage period.